KEHIDUPAN MASYARAKAT TRANSMIGRAN DI DESA RASAU JAYA TIGA KECAMATAN RASAU JAYA TAHUN 1976 - Harjanti, Diah Trismi; Aurellia, Stella Carolline; Childra, Girli Fifta; Khotimah, Khusnul; Mega, Maria (Universitas Tanjungpura, 2022)
The transmigration settlement in Rasau Jaya Tiga Village is through a general transmigration program, namely transmigration regulated by the government. The entry of transmigrants in the village of Rasau Jaya Tiga gave rise to various new cultures brought by the transmigrant community from outside the island. The existence of art from outside the island that entered the area of this Rasau Jaya Tiga, did not pose a problem to the local natives. The problem in this research is how the life of the transmigrant community in Rasau Jaya Tiga Village, Rasau Jaya District, Kubu Raya Regency in 1976. The method used is a descriptive qualitative research approach and data analysis techniques are carried out by means of data reduction. The results of this study are transmigrants from outside the island of Kalimantan who have settled in the village of Rasau Jaya Tiga through the transmigration program. This process and organized movement of people has had a huge impact on the development of transmigrant communities from all aspects of their lives. The main reason they transmigrate is none other than based on economic and welfare motives. In the initial process of the life of the transmigrant community, the first activity they carried out was mutual cooperation in cleaning the land around the housing location from the waste left over from residential development. In addition, in economic activity, many transmigrants manage land grants from the government to plant rice and vegetables.